2005
DOI: 10.1111/j.1742-4658.2004.04529.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial affinity for ADP is twofold lower in creatine kinase knock‐out muscles

Abstract: Excitable mammalian cells contain high activities of creatine kinase (CK, EC 2.7.3.2), which catalyses the reversible exchange of a phosphoryl group between phosphocreatine (PCr) and ATP. The tissue-specific CK enzymes are subcellularly compartmentalized and consist of three cytosolic dimers: BB-CK (brain-and smooth muscle-specific), MM-CK (muscle-specific) and MB-CK heterodimers. Furthermore, there is mitochondrial CK (Mi-CK) which is located in the intermembrane space of the mitochondrion and consists mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…With no restriction, the PSCR approaches a ratio of 1.0, which we observed in all mouse muscles (Fig. 5), as seen in other studies (ter Veld et al 2005;Aragonés et al 2008). We observed that human skeletal muscle presented with an average PSCR of 0.71, which is also comparable to other reported values (Boushel et al 2007).…”
Section: Figure 2 Respiratory Capacity and Control Between Mouse Quasupporting
confidence: 91%
“…With no restriction, the PSCR approaches a ratio of 1.0, which we observed in all mouse muscles (Fig. 5), as seen in other studies (ter Veld et al 2005;Aragonés et al 2008). We observed that human skeletal muscle presented with an average PSCR of 0.71, which is also comparable to other reported values (Boushel et al 2007).…”
Section: Figure 2 Respiratory Capacity and Control Between Mouse Quasupporting
confidence: 91%
“…Similar to the Crt −/y mice , mice deficient in both isoforms of CK showed non-significant reductions in stimulated respiration in cardiac fibers while showing increased respiration in muscle fibers (ter Veld et al 2005). Mice deficient in the Cr-synthesizing enzyme arginine:gylcine amidinotransferase (AGAT −/− ) show increased mitochondrial enzyme activity in the muscle.…”
Section: Discussionmentioning
confidence: 82%
“…Mitochondrial affinity for ADP is closely related to the mitochondrial capacity to respond to changes in cellular ATP demand. This parameter is usually determined in the literature by the calculation of apparent Km of respiration for ADP using either isolated mitochondria [9], [10], [11], [12], [13] or permeabilized cells [14], [15]. Indeed, for technical reasons, apparent Km for ADP is most of the time determined from the kinetic response of the respiratory chain activity (oxygen consumption) to the increase in ADP concentration.…”
Section: Introductionmentioning
confidence: 99%